A novel mechano‐enzymatic cleavage mechanism underlies transthyretin amyloidogenesis - Marcoux, Julien; Mangione, P Patrizia; Porcari, Riccardo; Degiacomi, Matteo T; Verona, Guglielmo; Taylor, Graham W; Giorgetti, Sofia; Raimondi, Sara; Sanglier‐Cianférani, Sarah; Benesch, Justin LP; Cecconi, Ciro; Naqvi, Mohsin M; et al. (EMBO molecular medicine, 2015)
The mechanisms underlying transthyretin‐related amyloidosis in vivo remain unclear. The abundance of the 49–127 transthyretin fragment in ex vivo deposits suggests that a proteolytic cleavage has a crucial role in destabilizing the tetramer and releasing the highly amyloidogenic 49–127 truncated protomer. Here, we investigate the mechanism of cleavage and release of the 49–127 fragment from the prototypic S52P variant, and we show that the proteolysis/fibrillogenesis pathway is common to several amyloidogenic variants of transthyretin and requires the action of biomechanical forces provided by the shear stress of physiological fluid flow. Crucially, the non‐amyloidogenic and protective T119M variant is neither cleaved nor generates fibrils under these conditions. We propose that a mechano‐enzymatic mechanism mediates transthyretin amyloid fibrillogenesis in vivo . This may be particularly important in the heart where shear stress is greatest; indeed, the 49–127 transthyretin fragment is particularly abundant in cardiac amyloid. Finally, we show that existing transthyretin stabilizers, including tafamidis, inhibit proteolysis‐mediated transthyretin fibrillogenesis with different efficiency in different variants; however, inhibition is complete only when both binding sites are occupied. Synopsis Selective proteolysis of TTR generates a highly amyloidogenic truncated protomer. Shear stress generated by turbulent flow of physiological fluids makes TTR susceptible to cleavage. This mechanism may play a crucial role in the development of cardiac TTR amyloidosis, and offers new therapeutic targets for treating the disease. Shear forces are required to prime proteolysis of wild‐type and other variant TTRs and to release the amyloidogenic fragment. These forces are present in the heart, offering an explanation for tissue specificity in cardiac TTR amyloidosis. TTR stabilizers, currently used to treat amyloidosis, can inhibit this mechanism; however, their efficacy differs for each variant. Graphical Abstract Selective proteolysis of TTR generates a highly amyloidogenic truncated protomer. Shear stress generated by turbulent flow of physiological fluids makes TTR susceptible to cleavage. This mechanism may play a crucial role in the development of cardiac TTR amyloidosis, and offers new therapeutic targets for treating the disease.